Implementation of Social Science Theory in Civic Education for School Students - Kurnia Imtichatus Sholichah; M. Turhan Yani; Harmanto Harmanto; Agus Suprijono (CV. Syntax Corporation Indonesia, 2024)
Civic education plays an important role in shaping Indonesian students into democratic, responsible and active citizens in social, political and economic life. Through an understanding of the political system, rights and responsibilities, community participation, social and cultural awareness, critical thinking, ethics, global citizenship and communication skills, citizenship education provides a foundation for students' active engagement and understanding of global roles. The purpose of this study is to identify and analyze the theories in social science that underlie citizenship education, as well as analyze how the application of social science can assist students in understanding and exercising their rights and responsibilities as citizens. This research uses a qualitative method with a literature study approach to examine the relationship between civic education and social science theories. The results show that the integration of social sciences such as sociology, psychology, education, politics and law in the civic education curriculum strengthens students' understanding of their rights and responsibilities. In addition, social sciences help advance civic engagement and responsibility, equipping students to face challenges in the 21st century. In conclusion, the application of Social Sciences in citizenship education prepares students to become informed and responsible citizens, capable of contributing positively in local and global communities.